2014
DOI: 10.1371/journal.pone.0106140
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Maternal Smoking on the Placental Expression of Genes Related to Angiogenesis and Apoptosis during the First Trimester

Abstract: ObjectiveMaternal cigarette smoking is reportedly associated with miscarriage, fetal growth restriction and placental abruption, and is paradoxically associated with a decreased risk of developing preeclampsia. In the present study, we investigated the gene expression levels of villous tissues in early gestation. We compared the expression levels of the genes related to angiogenesis and apoptosis in the villous tissues obtained from smoking and non-smoking pregnant women.Materials and MethodsWe collected villo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 49 publications
7
25
0
2
Order By: Relevance
“…We also found smaller but consistent reductions in early-term risk for exposure during the third trimester. These findings are supported by previous studies, which have shown that reducing smoke exposure during pregnancy improves birth outcomes, and that benefits are linked to when during pregnancy such reduction occurs 35 36…”
Section: Discussionsupporting
confidence: 89%
“…We also found smaller but consistent reductions in early-term risk for exposure during the third trimester. These findings are supported by previous studies, which have shown that reducing smoke exposure during pregnancy improves birth outcomes, and that benefits are linked to when during pregnancy such reduction occurs 35 36…”
Section: Discussionsupporting
confidence: 89%
“…Akihiko Sekizawa et al reported increased placental VEGF mRNA in first trimester placentas of smokers [17], however, when number of samples increased, no difference was found [15]. Previously, we found decreased Tie2/Ang1 in smoke exposed rat placentas of GD17 [19].…”
Section: Discussionmentioning
confidence: 79%
“…Smoking has been found to be strongly associated with increased risks of adverse perinatal outcomes, such as low BW and placental abruption 8 11 . The specific abnormalities that are caused by maternal smoking have been reported to provide additional insights into the genes and processes that are crucial for the formation of the feto-maternal interface in human pregnancy, leading to the adverse perinatal outcomes 9 . The present data also show that smoking was independently associated with placental abruption or being SGA when the same statistical analyses were performed.…”
Section: Discussionmentioning
confidence: 99%